2021
DOI: 10.3390/jmse9101118
|View full text |Cite
|
Sign up to set email alerts
|

Study on Hydrodynamic Coefficients of a Submarine Piggyback Pipeline under the Action of Waves and Current

Abstract: In this study, physical model tests are used to investigate the effects of a varying number of wave and current parameters, the gap ratios between the pipeline and seabed, the spacing ratios between the two pipelines and the diameter ratios on the hydrodynamic coefficients of the large, small pipeline and pipeline system (bundle) in a piggyback configuration under the combined action of waves and current. The results show that, compared with the pure wave field, the existence of the steady current will lead to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The inverse change was observed when α was increased from 90 • to 180 • . Cheng et al [5] examined the effects of gap distance between the pipeline and seabed, G/D, and d/D on the hydrodynamics a piggyback pipeline with α = 90 • in waves and currents in a wave flume. It was found that when G/D > 0.6, the effects of G/D on the hydrodynamics were weakened.…”
Section: Introductionmentioning
confidence: 99%
“…The inverse change was observed when α was increased from 90 • to 180 • . Cheng et al [5] examined the effects of gap distance between the pipeline and seabed, G/D, and d/D on the hydrodynamics a piggyback pipeline with α = 90 • in waves and currents in a wave flume. It was found that when G/D > 0.6, the effects of G/D on the hydrodynamics were weakened.…”
Section: Introductionmentioning
confidence: 99%